DEPRESI, PENYEBAB DAN GEJALA DEPRESI - Indah Rizki Ramadani; Tryana Fauziyah; Bima Khoirur Rozzaq (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
ThisThis research aims to determine the definition, causes and symptoms of depression. Semiotic research and approach is a method that examines and analyzes signs or symbols in a cultural or social context. Semiotics itself is the study of signs and their meaning. This approach views signs ascommunication media that create meaning in a society. This research examines the film "Daily Of The Sunshine". Depression is a condition where a person feels sad, disappointed when experiencing a change, loss or failure and becomes pathological when they are unable to adapt. Depression can occur due to many problems and social and cultural changes along with the rate of global growth, especially increasing technological advances. It cannot be denied that global technological advances have had both positive and negative impacts. Of course, we have to avoid negative impacts because it will lead to instability in life if someone does not have self-resilience which can cause depression for someone who experiences it.